The Relationship between Income Inequality and Poverty in Indonesia: A Sustainable Macroeconomic Analysis (Empirical Study of Java Island 2018–2022) - Astuty, Pudji; Priadana, Sidik; Saripah, Saripah; Bakti, Ilham Teruna (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the influence of income inequality, economic growth, and government expenditure on poverty levels in five provinces across Java Island during the period 2018–2022. A quantitative research approach with a panel data analysis method was employed, using the Fixed Effect Model (FEM) estimated through EViews 12 software. The study utilized secondary data obtained from the Central Bureau of Statistics (BPS) and the Ministry of Finance of the Republic of Indonesia. The results reveal that, partially, income inequality has a negative and significant effect on poverty, indicating that reducing inequality contributes to poverty alleviation. Conversely, economic growth shows a positive and significant relationship with poverty, suggesting that economic growth in Java has not been inclusive (non-pro-poor growth). Meanwhile, government expenditure has a negative and significant impact on poverty, demonstrating that increasing public spending—especially in social and infrastructure sectors—effectively reduces poverty when allocated efficiently. Simultaneously, all independent variables significantly affect poverty, with a Prob(F-statistic) of 0.000004 < 0.05. The coefficient of determination (R²) of 0.7419 indicates that 74.19% of poverty variation is explained by the model. The findings emphasize the importance of inclusive and equitable economic policies to support the achievement of the Sustainable Development Goals (SDGs), particularly Goal 1 (No Poverty) and Goal 10 (Reduced Inequalities).